2010
DOI: 10.1098/rsbl.2010.0144
|View full text |Cite
|
Sign up to set email alerts
|

Changes in age composition and growth characteristics of Atlantic sturgeon ( Acipenser oxyrinchus oxyrinchus ) over 400 years

Abstract: Populations of sturgeon (Acipenseridae) have experienced global declines, and in some cases extirpation, during the past century. In the current era of climate change and over-harvesting of fishery resources, climate models, based on uncertain boundary conditions, are being used to predict future effects on the Earth's biota. A collection of approximately 400-year-old Atlantic sturgeon spines from a midden in colonial Jamestown, VA, USA, allowed us to compare the age structure and growth rate for a pre-industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…For example, differences in productivity of stocks have been related to differences in temperature (Dutil and Brander 2003), and warming associated with global climate change was suggested to explain differences in the growth dynamics of a long-lived fish based on comparisons between colonial and modern samples (Balazik et al 2010). Impacts of temperature could be explained through several mechanisms.…”
Section: Resultsmentioning
confidence: 98%
“…For example, differences in productivity of stocks have been related to differences in temperature (Dutil and Brander 2003), and warming associated with global climate change was suggested to explain differences in the growth dynamics of a long-lived fish based on comparisons between colonial and modern samples (Balazik et al 2010). Impacts of temperature could be explained through several mechanisms.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, recent studies by Butler and colleagues revealed stable β cell mass across the adult human life span (28). Notably, some organisms such as specific kinds of Osteichthyes (bony fish) exhibit slow somatic growth that continues well after sexual maturity; sturgeon continue to grow slowly decades after sexual maturity (64). Could adult human β cells similarly harbor a capacity to slowly expand into adulthood?…”
Section: Figurementioning
confidence: 99%
“…The James River is the southernmost major tributary to the Chesapeake Bay. Historically, the James River supported a large population of Atlantic sturgeon, but loss of spawning habitat and overfishing coincided with dramatic in-system declines throughout the 19th and 20th centuries (Smith 1985;Balazik et al 2010). Observations in the 1990s of subadults caught by commercial fishers, as well as rare discoveries of dead adult Atlantic sturgeon in the James River (A. Spells, U.S.…”
mentioning
confidence: 99%